Inhibition of neutrophil extracellular trap formation attenuates NLRP1-dependent neuronal pyroptosis via STING/IRE1α pathway after traumatic brain injury in mice - Cao, Yiyao; Shi, Mingming; Liu, Liang; Zuo, Yan; Jia, Haoran; Min, Xiaobin; Liu, Xilei; Chen, Zhijuan; Zhou, Yuan; Li, Shenghui; Yang, Guili; Liu, Xiao; et al. (Frontiers in Immunology, 2023)
Introduction Increased neutrophil extracellular trap (NET) formation has been reported to be associated with cerebrovascular dysfunction and neurological deficits in traumatic brain injury (TBI). However, the biological function and underlying mechanisms of NETs in TBI-induced neuronal cell death are not yet fully understood. Methods First, brain tissue and peripheral blood samples of TBI patients were collected, and NETs infiltration in TBI patients was detected by immunofluorescence staining and Western blot. Then, a controlled cortical impact device was used to model brain trauma in mice, and Anti-Ly6G, DNase, and CL-amidine were given to reduce the formation of neutrophilic or NETs in TBI mice to evaluate neuronal death and neurological function. Finally, the pathway changes of neuronal pyroptosis induced by NETs after TBI were investigated by administration of peptidylarginine deiminase 4 (a key enzyme of NET formation) adenovirus and inositol-requiring enzyme-1 alpha (IRE1α) inhibitors in TBI mice. Results We detected that both peripheral circulating biomarkers of NETs and local NETs infiltration in the brain tissue were significantly increased and had positive correlations with worse intracranial pressure (ICP) and neurological dysfunction in TBI patients. Furthermore, the depletion of neutrophils effectively reduced the formation of NET in mice subjected to TBI. we found that degradation of NETs or inhibition of NET formation significantly inhibited nucleotide-binding oligomerization domain (NOD)-like receptor pyrin domain containing 1 (NLRP1) inflammasome-mediated neuronal pyroptosis after TBI, whereas these inhibitory effects were abolished by cyclic GMP-AMP (cGAMP), an activator of stimulating Interferon genes (STING). Moreover, overexpression of PAD4 in the cortex by adenoviruses could aggravate NLRP1-mediated neuronal pyroptosis and neurological deficits after TBI, whereas these pro-pyroptotic effects were rescued in mice also receiving STING antagonists. Finally, IRE1α activation was significantly upregulated after TBI, and NET formation or STING activation was found to promote this process. Notably, IRE1α inhibitor administration significantly abrogated NETs-induced NLRP1 inflammasome-mediated neuronal pyroptosis in TBI mice. Discussion Our findings indicated that NETs could contribute to TBI-induced neurological deficits and neuronal death by promoting NLRP1-mediated neuronal pyroptosis. Suppression of the STING/ IRE1α signaling pathway can ameliorate NETs-induced neuronal pyroptotic death after TBI.